продифференцировать данные функции.

katea001 katea001    3   11.01.2020 07:17    0

Ответы
ДаРуСя10 ДаРуСя10  11.10.2020 00:12

27*x^{2} - \frac{5}{x^{2} } + \frac{28}{x^{5} }+\frac{7}{3}*\sqrt[3]{x^{4} }

Пошаговое объяснение:

y=9*x^{3} +\frac{5}{x} -\frac{7}{x^{4} } +\sqrt[3]{x^{7} } \\y'=(9*x^{3} +\frac{5}{x} -\frac{7}{x^{4} } +\sqrt[3]{x^{7} } )'=9*(x^{3})' +5*(x^{-1})' -7*(x^{-4})' +(x^{\frac{7}{3} })'=\\=9*3*x^{3-1} +5*(-1)*x^{-1-1} -7*(-4)*x^{-4-1}+\frac{7}{3}*x^{\frac{7}{3} -1}=\\=27*x^{2} -5*x^{-2} +28*x^{-5}+\frac{7}{3}*x^{\frac{4}{3}}=\\=27*x^{2} - \frac{5}{x^{2} } + \frac{28}{x^{5} }+\frac{7}{3}*\sqrt[3]{x^{4} }

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика